THE EFFECT OF TRANSFERING ISRAEL CAPITAL CITY TO JERUSALEM TOWARD INDONESIA MACRO ECONOMY - Liliek Nur Sulistiyowati (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2019)
United States President Donald Trump has just issued a controversial policy by giving Jerusalem recognition as the capital of Israel. This controversial policy triggered a strong reaction from a number of countries, especially Islamic countries including Indonesia. Indonesia through President Jokowidodo strongly condemned the policy of moving the Israeli capital to Jerusalem because it would disrupt political and security stability in the Middle East region. In the midst of the political impact caused by President Donald Trump's policies also affected the global economy. The world stock exchanges reacted immediately with the existence of these policies, one of which was the fall of the stock market index in Japan and South Korea due to investor concerns. The impact of the policies implemented by President Donald Trump also affected the Indonesian economy. This policy will affect the financial markets and capital markets in Indonesia. Trump's policy triggered an increase in the US exchange rate against the currencies of other countries including the Indonesian currency. Some of the negative effects on the Indonesian economy were the increase in world crude oil prices. Indonesia is currently no longer an oil exporting country, so that with the increase in world crude oil prices it will provide a fiscal burden in the State Budget (APBN). Fuel subsidies in the state budget will increase along with the increase in world crude oil prices that occur. In addition to the impact on the rupiah exchange rate against the US , Donald Trump's policy also affects the inflation rate and the SBI interest rate. Through 2018, Bank Indonesia has raised the SBI interest rate by 150 basis points (bps) or 1.5%. The BI Governor explained that one reason for changing the benchmark interest rate was US monetary policy. The determination of high SBI interest rates also had an effect on reducing inflationary pressures. This study aims to look at the influence of President Donald Trump's policies regarding the transfer of the Israeli capital to Jerusalem against Indonesia's macroeconomic indicators. Indonesia's macroeconomic indicators are seen from 3 variables, such as the inflation rate, SBI interest rates and the rupiah exchange rate against US Key words : Donald Trump, inflation, SBI interest rates, exchange rates / exchange rates